Pengaruh Penggunaan Waktu Operasi Penangkapan yang Berdeda pada Alat Tangkap Bagan Tancap terhadap Hasil Tangkapan Ikan Teri (Stolephorus Sp) di Perairan Karangantu Serang Banten - Rhandy Rakasiwi; M Tajuddin Noor; Yusrudin Yusrudin (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2024)
Bagan stepper is a productive fishing tool for catching pelagic fish, especially anchovies. Utilization of existing resource potential can be improved by knowing the best transportation time, so it is necessary to analyze the level of effectiveness of the step-by-step fishing gear. The aim of this research is to determine the best transportation time for catches obtained using step-on fishing gear in order to improve the welfare of Karangantu fishermen. The method used in this research is the experimental fishing method by observing each treatment then calculating the weight (kg) of the catch using a step chart with 2 treatments (transport time 20.00 WIB and transport time 22.00 WIB) and 16 repetitions (trips). From the analysis results obtained, the calculated F value = 1.32, and the F table value = 1.15, so the data is not homogeneous. For the calculated t value = 0.10, and for the t table value = 3 then Ho is not rejected. So it can be concluded that there is a real difference between the anchovy catches using transportation times of 20.00 WIB and 22.00 WIB. Transport time 20.00 WIB provides the most fish catches